Factors Influencing IKEA Purchase Decisions in Malaysia: Analysis Pricing, Convenience, Consumer Experience, and Loyalty - Teoh, Kok Ban; Lew, Carol; Lok, Yee Huei; Lew, Yen Ru; Li, Haoran; Li, Jihan; Ali, Anees Jane; Mui Hung Kee, Daisy (The Global Academia Publisher, 2025)
This study investigates the factors influencing IKEA purchase decisions in Malaysia, focusing on pricing, convenience, consumer experience, and loyalty. The research analyzes how IKEA’s affordable pricing strategy enhances accessibility and consumer satisfaction. Convenience is examined through features like online ordering with pick-up points and well-designed store layouts, which reduce consumer effort and time. The study also explores the impact of IKEA’s digital platform, which allows free membership registration, providing benefits such as vouchers and exclusive gifts to foster consumer loyalty. Feedback collection through the website contributes to continuous improvement in consumer experience. This research offers insights into the effectiveness of these strategies and their role in shaping purchase decisions in Malaysia. Findings contribute to a deeper understanding of consumer behavior and provide actionable recommendations for enhancing retail strategies in the furniture industry.